Mainstreaming the environment : the World Bank Group and the environment since the Rio Earth Summit (World Bank WashingtonUS, 1995)
Addresses progress in those areas of financing and technical assistance that are targeted specifically toward the environment. Focuses on the extent to which environmental concerns are incorporated into the entire portfolio of the Bank's activities. Examines how the International Finance Corporation and the Multilateral Investment Guarantee Agency addresses environmental concerns in their private sector activities.
Bibliography: 289-301 p.